If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 87 + 94y + -2 = -6(-16y + -27) + 6 Reorder the terms: 87 + -2 + 94y = -6(-16y + -27) + 6 Combine like terms: 87 + -2 = 85 85 + 94y = -6(-16y + -27) + 6 Reorder the terms: 85 + 94y = -6(-27 + -16y) + 6 85 + 94y = (-27 * -6 + -16y * -6) + 6 85 + 94y = (162 + 96y) + 6 Reorder the terms: 85 + 94y = 162 + 6 + 96y Combine like terms: 162 + 6 = 168 85 + 94y = 168 + 96y Solving 85 + 94y = 168 + 96y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-96y' to each side of the equation. 85 + 94y + -96y = 168 + 96y + -96y Combine like terms: 94y + -96y = -2y 85 + -2y = 168 + 96y + -96y Combine like terms: 96y + -96y = 0 85 + -2y = 168 + 0 85 + -2y = 168 Add '-85' to each side of the equation. 85 + -85 + -2y = 168 + -85 Combine like terms: 85 + -85 = 0 0 + -2y = 168 + -85 -2y = 168 + -85 Combine like terms: 168 + -85 = 83 -2y = 83 Divide each side by '-2'. y = -41.5 Simplifying y = -41.5
| 10x-27=20 | | (x-2)(x+1)=(2x-5)+1 | | 3[4x+3]=2x-5[3-x]+2 | | a^2-2ax+x^2-9=0 | | -9(-2q-73)-83q=8(-8q+65) | | 2(4x+7)=5x+44 | | 8*x+9=33 | | 10+6x=-6x-50 | | [(2x+5)+3y][(2x+5)-3y]=0 | | 14.5=5n-2 | | 8x+6+2x=12+4x | | 4x-8=8x+7-7x | | 5(-17c+53)=-7(5c-45) | | 120=x | | 121=-8m+7(1-7m) | | -10-1=7x-5-x | | -18.04-4.9v+1.6v=14.7v+4(-18.1v+19.97) | | X(a+3)+y(a+3)=0 | | -3(8-11j)=-5(12-6j) | | -3=3x-6x+18 | | 4y-8x=10 | | 55x-11y=253 | | -3(8-11j)=-5(12-j) | | -5d+19-4d=-6(4d+19)-4d | | 8x-15-4x=13 | | 15x+(15)=6 | | 5(-6n+3)=165 | | -4(-18+6n)=-6(13n+15) | | 3x-7=14+2 | | 4x-4-x=-4 | | 11-3s=8 | | 1(-7x+1)=-55 |